Precarious life : the powers of mourning and violence - Butler, Judith, 1956- (Verso, 2004)
In this profound appraisal of post-September 11, 2001 America, Judith Butler considers the conditions of heightened vulnerability and aggression that followed from the attack, and the US government's decision to retaliate. She critiques the use of violence that has emerged as a response to loss, and argues that the dislocation of first-world privilege offers instead a chance to imagine a world in which that violence might be minimized, and in which interdependency becomes acknowledged as the basis for a global political community.